Cancer therapy combination: green tea and a phosphodiesterase 5 inhibitor? - Chung S. Yang; Hong Wang (The Journal of Clinical Investigation, 2013)
The major constituent of green tea, (–)-epigallocatechin-3-O-gallate (EGCG), has been shown to have cancer-preventive and therapeutic activities. Numerous molecular targets for EGCG have been proposed, but the mechanisms of its anticancer activities are not clearly understood. In this issue of the JCI, Kumazoe et al. report that EGCG activates 67-kDa laminin receptor (67LR), elevates cGMP levels, and induces cancer cell apoptosis. Furthermore, a phosphodiesterase 5 inhibitor, vardenafil, synergizes with EGCG to induce cancer cell death. This is a provocative observation with important implications for cancer therapy. It also raises several issues for further investigation, such as the mechanism by which EGCG specifically activates 67LR.